Fabrication characterization and potential applications of carbon nanoparticles in the detection of heavy metal ions in aqueous media. (February 2018) - Simpson, Aaron; Pandey, R.R.; Chusuei, Charles C.; Ghosh, Kartik; Patel, Rishi; Wanekaya, Adam K.
Abstract: Carbon nanoparticles were prepared from glycerol by a thermal process in the presence of H3 PO4 . These particles were spherical with an average diameter of 66 nm and consisted of a carbon core with carboxylic acid and alcohol functional groups on the surface. The particles were characterized using Fourier-transform infrared, electron microscopy, X-ray diffraction, light scattering, ultraviolet–visible, fluorescence, and X-ray photoelectron spectroscopy techniques. Glassy carbon electrodes were modified, by drop casting, with the carbon nanoparticles and used for heavy metal detection with square wave anodic stripping voltammetry. Parameters such as accumulation (pre-concentration) time, amount of carbon nanoparticles casted, reduction time and reduction potential were optimized. Potential application of these glassy carbon electrodes modified with carbon nanoparticles for electrochemical analysis was demonstrated by the detection of heavy metal ions in tap water. The average recoveries of Pb 2+ and Cu 2+ in spiked tap water samples were 98.2% and 96.7% with a relative standard deviations of 7.4% and 8.5%, respectively. Graphical abstract: Image 1